2017
DOI: 10.1016/j.bbi.2016.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Toxoplasma gondii seropositivity and acoustic startle response in an inner-city population

Abstract: Toxoplasma gondii (TOXO) is a neuroinvasive protozoan parasite that induces the formation of persistent cysts in mammalian brains. It infects approximately 1.1 million people in the United States annually. Latent TOXO infection is implicated in the etiology of psychiatric disorders, especially schizophrenia (Scz), and has been correlated with modestly impaired cognition. The acoustic startle response (ASR) is a reflex seen in all mammals. It is mediated by a simple subcortical circuit, and provides an indicato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…According to Fig 2, the lowest and highest ORs are related to the studies performed by Massa et al . [46] and Conejero-Goldberg et al . [22], respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Fig 2, the lowest and highest ORs are related to the studies performed by Massa et al . [46] and Conejero-Goldberg et al . [22], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…used a larger sample size with a different set of psychiatric diagnoses. Moreover, race, educational level, and economic status can result in different ORs [46].…”
Section: Discussionmentioning
confidence: 99%
“…However, a slowing of latency is not unique to schizophrenia. It has been reported in autism ( 32 , 33 ), Huntington’s disease ( 34 ), and post-traumatic stress disorder ( 25 , 35 ). It is unknown how closely the neural underpinnings of slowed latency in schizophrenia may overlap with that of these other disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, other experimental studies also found that dopaminergic neurons containing T. gondii have demonstrated an increased synthesis of dopamine and an elevated presence of homovanillic acid, a dopamine metabolite (Stibbs, 1985; Prandovszky et al, 2011; Martin et al, 2015). A recent study reported a higher acoustic startle response magnitude among T. gondii infected participants (Massa et al, 2017). The authors proposed that the finding might be the outcome of increased dopamine production (Swerdlow et al, 1986; Parlog et al, 2015).…”
Section: Introductionmentioning
confidence: 98%